LEADERSHIP DECISION MAKING STYLES FOR INDIAN BUSINESS ECOSYSTEM - Phukan, Pranjal Kumar (Digital Repository of Theses - SSBM Geneva, 2023)
This research aims to look into various aspects of leadership ideologies and how they relate to the efficiency of selected Indian business sector workers. High-performing leaders may build high-performing teamwork by employing the right leadership style. The framework for leadership conduct in the Indian business ecosystem will be suggested with the aid of this research. This study aimed to identify the key variables that affect organizational leadership judgment. This portion of the paper analyses the findings and considers pertinent literature to establish a pattern of significance for this research. The research summarized management ideas in this work by contrasting judgment with leadership style. Earlier research on the judicial process has centered on analyzing the procedure and seeking clarifications on the following: What is the practice in which a substance? Is it moral, logical, sentimental, social, or information? Investigators concentrated on the different aspects that influenced judgment and their impacts, one of which was the requirement for sustainability and the preservation of the biological environment. The contributions to the advancement of science clarify current debates about study themes, including management techniques, choice, society, and pro-ecological tactics. The research added some ideas and illustrations to the earlier literature reviews in which the research suggested a drawing-based approach to the researched topics. The research discussed how managerial style and company culture relate, including leadership and supervisory responsibilities. The research added a judgment process that included factors, management styles, and their influence on the judgment chain. Additionally, several recommendations are made for additional research focusing on the pro-ecological approach. One might concentrate their study on examining the variables that affect managers' judgment and what variables determine the firm's management style. By putting such knowledge into practice, the company's management may be shaped and the judgment process supported. Scholars may expand their research to include several Association of South East Asian Nations and South Asian Association for Regional Cooperation members. To uncover unknown details about leaders' DMS, a future study may also be conducted on a continuous examination in transitioning industries.